Acacia leucophloea Willd and Acacia alba Willd-Two Species or One - Jacob, K. Cherian (Indian Forester, 1941)
From the Forester's, and perhaps the Agriculturist's, point of view, temperatures. Relative humidities, rainfall and rainy days, even dri les under one-tenth of an inch, and heavy dews in the tropics are important factors to study for the proof of climatic change. Of these factors rainfall change is the most difficult to establish, as the annual or seasonal fluctuations may be greater than the changes which the change of ground cover produces. This article shows how a knowledge of the length of the climatic rainfall cycle enables annual fluctuation in graphical form to be smoothed out, thus facilitating the detection of rainfall change.